Studi Komparatif Gender : Perilaku Pembelian Green Product The Body Shop Di Pontianak - admin, Dwiyati B1021131029 (Jurnal Manajemen Update, 2017)
This study aims to examine and analyze the influence of variables Environmental Attitude, Environmental Concern, Perceived Seriousness of Environmental Problems, Perceived Environmental Responsibility, Peer Influence and Self Identity in Environmental Protection against the Green Purchasing Behavior on green product of The Body Shop in the city of Pontianak. This study is causal research. The population in this study are all consumers of The Body Shop, both men and women who reside in Pontianak today. This study uses judgment sampling technique and purposive sampling with a sample size of 150 people, divided by gender with each category are 75 men and 75 women. The analysis technique used is multiple regression analysis using SPSS version 16. Data processing results obtained show that the Environmental Attitude, Environmental Concern, Perceived Environmental Responsibility, Peer Influence and Self Identity in Environmental Protection significant effect on Green Purchasing Behavior on green product of The Body Shop. While Perceived Seriousness of Environmental Problems no significant effect on Green Purchasing Behavior on green product of The Body Shop. In addition, the processing of the data also show that there are differences between men and women in the Green Purchasing Behavior on green product of The Body Shop. Women showed a higher value on the Environmental Attitude, Environmental Concern, Perceived Environmental Responsibility, Peer Influence, Self Identity in Environmental Protection and Green Purchasing Behavior at The Body Shop green products than men. But the man showed higher value on the Perceived Seriousness of Environmental Problems at The Body Shop green products than women. The findings of this study prove that the Environmental Attitude (X1), Environmental Concern (X2), Perceived Environmental Responsibility (X4), Peer Influence (X5) and Self Identity in Environmental Protection (X6) in this study serves as a variable that affects the Green Purchasing Behavior ( Y). Keywords : Environmental Attitude, Environmental Concern, Perceived Seriousness of Environmental Problems, Perceived Environmental Responsibility, Peer Influence, Self Identity in Environmental Protection, Green Purchasing Behavior